Construction and validation of an angiogenesis-related lncRNA prognostic model in lung adenocarcinoma - Gong, Quan; Huang, Xianda; Chen, Xiaobo; Zhang, Lijuan; Zhou, Chunyan; Li, Shijuan; Song, Tingting; Zhuang, Li (Frontiers in Genetics, 2023)
Background: There is increasing evidence that long noncoding RNAs (lncRNAs) can be used as potential prognostic factors for cancer. This study aimed to construct a model based on angiogenesis-related lncRNAs for risk assessment and prognostic analysis of patients with lung adenocarcinoma (LUAD). Methods: LUAD-related transcriptome data were obtained from TCGA and GEO. A prognostic signature based on multiple angiogenesis-related lncRNAs was constructed through differential expression analysis, overlap analysis, Pearson correlation analysis, and Cox regression analysis. The validity of the model was assessed using K-M and ROC curves. Independent external validation of the model was also performed in the GSE30219 dataset. Prognostic lncRNA-microRNA (miRNA)-messenger RNA (mRNA) competing endogenous RNA (ceRNA) networks were identified. Analyze immune cell infiltration and mutational characteristics. Quantitative real-time PCR (qRT-PCR) gene arrays were utilized to detect the expression of four human angiogenesis-associated lncRNAs. Results: A total of 26 aberrantly expressed angiogenesis-related lncRNAs in LUAD were identified. Subsequently, we constructed a Cox risk model with good predictive performance based on LINC00857, RBPMS-AS1, SYNPR-AS1, and LINC00460, which may be an independent prognostic predictor for LUAD. The low-risk group was characterized by a significant association with good prognosis, a relatively higher abundance of resting immune cells, and a lower expression of immune checkpoint molecules. Moreover, we predicted 105 ceRNA mechanisms based on four prognostic lncRNAs. qRT-PCR results showed that LINC00857, SYNPR-AS1, and LINC00460 were significantly highly expressed in tumor tissues and RBPMS-AS1 was highly expressed in paracancerous tissues. Conclusion: A risk model based on four angiogenesis-related lncRNAs could serve as a promising prognostic biomarker for LUAD patients.